2015
DOI: 10.5505/tjtes.2015.94224
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Medical Technicians And Paramedics Encountered Work-Related Injuries in Turkey

Abstract: BACKGROUND: Evaluated in the present study were locations, descriptions, and results of work-related injuries (WRIs) sustained by emergency medical technicians (EMTs) and paramedics in Turkey's most crowded city, İstanbul.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 12 publications
0
6
0
Order By: Relevance
“…2% reported assault by weapon; assault with a weapon was also described in the literature evaluating workplace violence among EMS workers. [3,14,22] Patients' relatives were responsible for the majority of the attacks, accounting for more attacks than the patients identified as attackers in our report. Among participants who were physically harmed, only 7% reported the event.…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…2% reported assault by weapon; assault with a weapon was also described in the literature evaluating workplace violence among EMS workers. [3,14,22] Patients' relatives were responsible for the majority of the attacks, accounting for more attacks than the patients identified as attackers in our report. Among participants who were physically harmed, only 7% reported the event.…”
Section: Discussionmentioning
confidence: 79%
“…[14][15][16] In our study, we reported that members of the general public were involved in verbal abuse, which indicated a trend, especially in the Middle East. [22] Regarding verbal abuse, 60% of the study participants were subjected to verbal abuse during their shift. Almost 70% of the participants were exposed to verbal threats between one and three times, and approximately 14% reported being exposed multiple times.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the nature of their work, public safety personnel (PSP; e.g., correctional workers, police officers, firefighters, paramedics, public safety communications officials [e.g., 911 call center operators/dispatchers]) are commonly exposed to potentially traumatic events. [1][2][3][4][5][6][7][8][9] Studies across various samples demonstrate high estimates of trauma exposure among PSP, exceeding 85%; 1,3,[7][8][9] a recent study found that PSP reported exposure to 11 of the 16 types of traumatic events, on average. 1 Extant research has highlighted the negative health correlates associated with trauma exposure among PSP and the general population, including psychiatric illnesses 1,[6][7]10,11 and, of particular relevance to the current study, physical conditions.…”
Section: Abstract Public Safety Personnel Trauma Exposure Physical Conditionsmentioning
confidence: 99%
“…In a study with emergency medical technicians and paramedics in Istanbul, 52.2% reported at least one needle-stick injury in the past two years. 33 The most common causes for such injuries provided by respondents were working in a cruising ambulance and the need to do things quickly.…”
Section: Discussionmentioning
confidence: 99%